The Effect of Think Pair Share Learning Model to Improve Student’s Problem-Solving Ability - Nafida Hetty Marhaeni; Sarah Vega Ramos; Totok Triyadi; Bayu Sudarmaji (Universitas Mercu Buana Yogyakarta, 2022)
Problem solving skills are useful for training students to face increasingly complex problems. Learning models that have not been able to stimulate these abilities need to be applied. Thus, the purpose of this study was to determine the effect of the Think Pair Share learning model to improve students' problem solving abilities. This type of research is experimental research with pretest posttest control group design. The samples in this study were class VIIIA students as the experimental class and class VIIIC students as the control class, each class totaling 32 students. Data collection techniques used interviews, observations, and problem-solving ability test questions on the Pythagorean theorem material. The results showed that the application of the Think Pair Share learning model has been proven to be effective in improving students' problem solving abilities. Based on the results of the increase in students' problem-solving ability tests, the experimental class was higher than the control class (32.5 21.88). In addition, the application of the Think Pair Share learning model gives students more time to think deeply about what is being explained or experienced (thinking, answering, and helping each other). In addition, the TPS learning model also provides opportunities for students to think deeply and can help each other.